Urban shared energy systems and behaviour change − simulating a common pooled resource problem. Issue 1 (31st July 2019) - Burton, Craig Alexander; Ryan, Christopher; Rismanchi, Behzad; Candy, Seona
Abstract : Purpose: The purpose of this paper is to test a new methodology for simulating shared electricity generation among small groups of neighbours with Ostrom's (1994) principles of common pool resource (CPR) (human behaviour-based) efficiencies. The approach does not anticipate exclusive off-grid communities but instead, diverse energy users taking advantage of the averaging effects of aggregation, the social benefits of a CPR and direct action on emissions. Design/methodology/approach: The study tested three groups of five adjacent − or same-building − neighbours for three months to measure how electricity demand (import) is affected by an in-home display issuing nudges and sanctions by the group around a simulated (limited capacity) shared solar and battery system. A control group of six homes' energy data was obtained for the same period. Findings: Two groups reduced their energy demand with weak but significant correlation between stimulus and reduced energy demand and one group increased demand. There were no significant effects in time-of-use behaviours. Research limitations/implications: The study shows that the interaction between consumers and energy systems can in this instance be simulated with inexpensive equipment. Studying dynamic interactions between people and systems provides new data where supply simulations have been one-sided. There is support in this work that the energy supply can be presented as a rivalrous commons system. Practical implications: Urban adjacent neighbours (and apartment occupants in the same building or campus) exhibit emergent group behaviours around electricity use conservation and time-of-use. Managing energy demand is very difficult but very important for making consumer behaviour "fit" the future supply of energy which may be unreliable and limited. Social implications: There are likely social benefits and other overflow benefits when neighbours can share a critical resource. There are other critical services that may be managed according to the Ostrom commons principles. The sharing group will be more resilient in terms of electricity but also in terms of social capital. Originality/value: The work builds on the work of Rachel Coxcoon and others who have identified that groups perform better at certain challenges than individuals do. This aligns with scale and operational efficiencies in shared renewable energy infrastructure. Shaping behaviour and the generation systems together for optimal outcomes is new work.